2014
DOI: 10.1371/journal.pone.0095894
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between the Family Education and Mortality of Patients on Peritoneal Dialysis

Abstract: AimsTo investigate whether education level of family members predicts all-cause and cardiovascular death and initial-episode peritonitis in patients on peritoneal dialysis (PD).MethodsA total of 2264 patients on chronic PD were collected from seven centers affiliated with the Socioeconomic Status on the Outcome of Peritoneal Dialysis (SSOP) Study. All demographic, socioeconomic and laboratory data of patients and the education level of all family members were recorded at baseline. Multivariate Cox regression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
(32 reference statements)
0
10
0
2
Order By: Relevance
“…Kim et al (28) showed that a ‘lower level of education’ (as defined by an academic background of ‘middle school or lower’) of the patients was an independent risk factor for PD-catheter-associated peritonitis and technique failure. Yang et al (29) discovered that the level of family members’ education strongly predicted PD outcome, with higher level of patient and family education being associated with significantly better outcomes following PD-catheter insertion. These are important findings which highlight the importance of good education for both patients and their family members.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (28) showed that a ‘lower level of education’ (as defined by an academic background of ‘middle school or lower’) of the patients was an independent risk factor for PD-catheter-associated peritonitis and technique failure. Yang et al (29) discovered that the level of family members’ education strongly predicted PD outcome, with higher level of patient and family education being associated with significantly better outcomes following PD-catheter insertion. These are important findings which highlight the importance of good education for both patients and their family members.…”
Section: Discussionmentioning
confidence: 99%
“…89 The role and education of family and carers are highly relevant and should be included in this support. 90 To facilitate PD as a patient-preferred treatment, assisted PD should be considered as an option. 81,83 For patients residing in rural and remote locations, electronic communication methods could also be used for monitoring and support.…”
Section: Patient Education and Continuous Supportmentioning
confidence: 99%
“…Over 60% of patients use PD outside of standard office hours, so providing 24 h support is essential for safe and effective care 7 days a week . The role and education of family and carers are highly relevant and should be included in this support . To facilitate PD as a patient‐preferred treatment, assisted PD should be considered as an option .…”
Section: Improving Patient Outcomesmentioning
confidence: 99%
“…Yang et al . [10] emphasized that family members’ education level was important for mortality outcome of PD patients. There were conflicting results as regards the association between education level and PD outcomes.…”
Section: Introductionmentioning
confidence: 99%